Cover Image, Volume 173A, Number 11, November 2017. Issue 11 (20th October 2017) - Justice, Cristina M.; Kim, Jinoh; Kim, Sun‐Don; Kim, Kyunhgho; Yagnik, Garima; Cuellar, Araceli; Carrington, Blake; Lu, Chung‐Ling; Sood, Raman; Boyadjiev, Simeon A.; Wilson, Alexander F.
Abstract : The cover image, by Cristina M. Justice et al., is based on the Original Article A Variant Associated with Sagittal Nonsyndromic Craniosynostosis Alters the Regulatory Function of a Non‐Coding Element, DOI:10.1002/ajmg.a.38392 . Photo Credit: Blake Carrington (NIH/NHGRI).